Accelerated iTBS with a personalised targeting method to treat negative symptoms of schizophrenia: A randomized controlled trial - Yunyi Han; Fang Jin; Jimmy Lee; Wenpeng Hou; Xue Yang; Yiming Zhang; Yueying Zhang; Xuefeng Lu; Zhimin Wang; Qijing Bo; Zhengyi Yang; Fuchun Zhou; et al. (Brain Stimulation)
Background: The efficacy of non-invasive brain stimulation in ameliorating schizophrenia's negative symptoms remains to be validated. The mesocortical pathway, mostly comprising the ventral tegmental area (VTA) and prefrontal cortex, is the core neural circuit underlying negative symptoms. This study aimed to assess the clinical and biological effects of accelerated intermittent theta burst stimulation (iTBS) targeted to the dorsolateral prefrontal cortex (dlPFC), guided by personalised dlPFC-VTA functional connectivity (FC). Methods: Eighty schizophrenia patients with predominant negative symptoms received 40 sessions of either active (n = 40) or sham (n = 40) accelerated iTBS (1800 pulses) in two weeks, targeting the region of the left dlPFC most functionally correlated with the VTA. Clinical and cognitive follow-ups occurred at week 4, 8, and 12. The primary outcome was the alteration in PANSS negative symptom (PANSS-NS) scores at week 4, while secondary outcomes included additional clinical, cognitive assessments and neuroimaging alterations. Results: At week 4, the active group showed a significant reduction in PANSS-NS compared to the sham group, with a significant group × time interaction effect (P < 0.001, mean difference = 4.10, Cohen's d = 0.83). At week 2, compared to the sham group, the active group exhibited reduced left temporal middle gyrus (TMG) (r = −0.29, p = 0.01) activation and FC between the VTA and left TMG (r = −0.34, p = 0.003), and both were negatively correlated with PANSS-NS changes in both groups. Conclusion: Accelerated iTBS targeting the personalised region determined by dlPFC-VTA FC is an effective intervention to alleviate negative symptoms of schizophrenia.